On the chaotic behaviour of a prototype delayed dynamical system - Uçar, A (Pergamon-Elsevier Science Ltd, 2003)
A simple model described by an autonomous continuous-time difference-differential equation with one variable is proposed as a chaos generator and is studied in this paper. A novel diagram is presented to obtain the desired solution mode/modes for a range of the model parameters. Qualitatively preserved solution mode lines have been introduced and depicted in the diagram. It leads to choose the desired behaviours without performing extensive simulations. (C) 2002 Elsevier Science Ltd. All rights reserved.
Keywords: Time-Delay; Bifurcations; Oscillations; Stability; Circuit